Quality Problems, Policies, and Attitudes in the United States and Japan: An Exploratory Study - Garvin, David A. (Academy of Management Journal, 1986)
This study drew on surveys of first-line supervisors in a single, broadly representative industry to compare practices and attitudes concerning quality in the United States and Japan. It focused on two central issues: (1) the changing mix of problems with quality as quality performance improves; and (2) the relationships between management commitment to quality, workforce commitment to quality, pressure to produce goods of high quality, and quality performance.